A new species and new records of the subtribe Lebinthina (Grylloidea, Eneopterinae, Lebinthini) from Mindanao, Philippines - Bahoy, Daphne Cayle M.; Sabang, Aira Mae M.; Tan, Ming Kai; Nuñeza, Olga Macas; Robillard, Tony (Zootaxa, 2024)
A new species of Falcerminthus is described from Zamboanga del Norte in western Mindanao: Falcerminthus hispidus sp. nov. We also present a new locality record for Falcerminthus parvus (Baroga-Barbecho & Robillard, 2020) in the south of Mindanao, i.e., South Cotabato, Lake Sebu; and Lebinthus luae Robillard & Tan, 2013 in Mindanao.